Short Communication: Molecular characterization and blood hematology profile of dogs infected by Ehrlichia canis in Yogyakarta, Indonesia - yustinus oswin primajuni wuhan; Aris Haryanto; Ida Tjahajati (Society for Indonesian Biodiversity, 2020)
Abstract. Wuhan YOP, Haryanto A, Tjahajati I. 2020. Short Communication: Molecular characterization and blood hematology profile of dogs infected by Ehrlichia canis in Yogyakarta, Indonesia. Biodiversitas 21: 3242-3248. Ehrlichia canis is Gram-negative intracellular obligate bacteria that cause ehrlichiosis, a companion vector-borne disease is a potentially fatal disease that attacks dogs. The purpose of this study was to molecular characterize and determine the features of Ehrlichia-infected blood based on the amplification of the gltA gene in Ehrlichia infected dogs from Yogyakarta, Indonesia. Blood samples were collected from 51 dog patients from the Prof. Dr. Soeparwi Animal Hospital, animal clinics, and pet shops based on the anamnesis, clinical sign, and physical examination, followed by microscopic examination, routine hematology, PCR amplification, and DNA sequencing were carried out on the blood samples. Based on positive PCR amplification and blood hematology profile examination ehrlichiosis-positive in dogs showed that thrombocytopenia case was 82.3%, anemia was 70.5%, eosinopenia was 70.5%, neutropenia was 29.4%, monocytopenia was 23%, leukopenia was 17% and lymphopenia was 11.7%. Morulae of Ehrlichia sp.was not found in microscopic examination. Molecularly, detected of E. canis using the gltA gene showed that 34% of samples were positive results. Then 5 of positive Ehrlichia samples were DNA sequenced, they showed a high homology of 100% with Hat Yai isolates (KU765199.1). There was no genetic diversity between E. canis samples in Yogyakarta.